1996
DOI: 10.1634/theoncologist.1-1-41
|View full text |Cite
|
Sign up to set email alerts
|

Staging Laparotomy in the Management of Hodgkin's Disease: Is it Still Necessary?

Abstract: Approximately 3,500 cases of stage I and II Hodgkin's disease are diagnosed each year in the United States. Traditionally, those patients who are considered candidates for primary radiation therapy undergo staging laparotomy (pathologic staging) to rule out definitively the presence of occult subdiaphragmatic disease. An appreciation of the risks of laparotomy and a recognition of the effectiveness of salvage chemotherapy in patients who fail primary radiation therapy have permitted the increased use of clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 139 publications
(268 reference statements)
0
4
0
Order By: Relevance
“…This strategy accepts the morbidity of salvage chemotherapy and ignores the observation that the stage of HD will be changed by laparotomy in 30% of patients. 2 A review of staging laparotomy by Multani and Grossbard 11 showed a mortality of 0.3% to 1%, major morbidity of 3% to 18%, and minor morbidity of 6% to 19%. Morbidity-related delays of subsequent treatment occurred in 5% to 10% of patients.…”
Section: Commentmentioning
confidence: 99%
“…This strategy accepts the morbidity of salvage chemotherapy and ignores the observation that the stage of HD will be changed by laparotomy in 30% of patients. 2 A review of staging laparotomy by Multani and Grossbard 11 showed a mortality of 0.3% to 1%, major morbidity of 3% to 18%, and minor morbidity of 6% to 19%. Morbidity-related delays of subsequent treatment occurred in 5% to 10% of patients.…”
Section: Commentmentioning
confidence: 99%
“…As the long-term complications caused by treatments, radiation therapy has been reported to increase the potential of developing lung and breast cancers, and long-term complications due to a splenectomy (21,22) and chemotherapy the incidence of cardiac and pulmonary diseases, and sterility (23).…”
Section: Discussionmentioning
confidence: 99%
“…In selected situations, as in bulky mediastinal disease, both chemotherapy and radiotherapy are usually recommended [3][4][5][6][7]. A recent review in this journal made the case for avoiding staging laparotomy for supradiaphragmatic, nonbulky clinical stage I or II patients [8]. We believe that an alternative point of view also deserves consideration.…”
mentioning
confidence: 99%
“…The utility of staging for Hodgkin's disease has been debated over the past 30 years, and it is again the issue of debate in the recent scholarly publication by Multani and Grossbard [8]. The necessity of staging laparotomy is again questioned.…”
mentioning
confidence: 99%